ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEMERINTAHAN DESA DALAM PEMBINAAN DAN PEMBERDAYAAN MASYRAKAT DESA (STUDI KASUS DI DESA BATU TERING KECAMATAN MOYO HULU KABUPATEN SUMBAWA NTB) - DEDI SUPRIADI (GANEC SWARA, 2024)
This research was conducted in Batu Tering Village, Moyu Hulu District, Sumbawa Regency, West Nusa Tenggara. The research methods using descriptive qualitative. The purpose of this study is to find out what factors influence the village government in fostering and empowering the village community, while the results of the study found that there are several factors that influence the empowerment and development of the society in Batu Tering Village community, namely Internal Factors and External Factors